P17 Clinical evidence supported by a model-based approach and real world data for the development of c.e.r.a. (continuous erythropoietin receptor activator) in pediatric patients with anemia due to chronic kidney disease. Issue 6 (17th May 2019) - Chanu, P; Weichert, A; Schaefer, F; Meyer Reigner, S; Reigner, B; Frey, N
Abstract : Background: C.E.R.A. indicated in Chronic Kidney Disease adult patients to correct and maintain hemoglobin (Hb) levels is approved in Europe and US since 2007; pediatric development is ongoing. A 20-week open-label Phase II study (NH19707) of intravenous (IV) C.E.R.A. in patients aged 5–17 years was conducted and data collected was analysed with adult data 1 . Objectives were to determine the pharmacokinetic/pharmacodynamic (PK/PD) characteristics of C.E.R.A. in a broad population, to simulate treatment outcomes of C.E.R.A. administered IV and subcutaneous (SC) in pediatric patients and compare them to NH19707 data and Real World Data (RWD). Methods: PK and Hb data from 63 pediatric patients were pooled with 400 adult patients IV and SC data and analysed using models previously developed in adults 2 . Simulations of treatment outcomes with C.E.R.A. administered IV and SC were performed. Assumptions on SC bioavailability in pediatric patients were based on previous darbepoetin data 3 . Model inferences were challenged versus RWD obtained in 158 pediatric patients receiving C.E.R.A. SC (N=126) or IV (N=32) from registries maintained by the International Pediatric Dialysis Network (IPDN, www.pedpd.org). Results: The adult PK and PK/PD models adequately described the pediatric data and indicated a similar exposure-response relationship in both populations. C.E.R.A. doses were adjusted to Hb levels during the simulation process to reflect clinical practice; simulated Hb levels matched observations. Furthermore, simulated median monthly C.E.R.A. doses following Hb stabilization were 105 µg (95% prediction interval 72–159 µg) for SC and 84 µg (60–123 µg) for IV, in good agreement with those reported in the IPDN registry: 100 µg and 80.4 µg, respectively. Conclusion: The PK/PD characteristics of C.E.R.A. are similar between adult and pediatric populations. Simulations of clinical outcomes in accordance with clinical trial data and RWD provided sufficient clinical evidence to support pediatric plans optimization subsequently approved by FDA and EMA. References: 1.Fischbach M, Wühl E, Reigner SCM, Morgan Z, Schaefer F. Efficacy and long-term safety of C.E.R.A. maintenance in pediatric hemodialysis patients with anemia of CKD. Clin J Am Soc Nephrol. 2018;13(1):81–90. Chanu P, Gieschke R, Charoin JE, Pannier A, Reigner B. Population pharmacokinetic/pharmacodynamic model for C.E.R.A. in both ESA-naïve and ESA-treated CKD patients with renal anemia. Journal of Clinical Pharmacology. J Clin Pharmacol . 2010;50(5):507–520. 3.Amgen Inc. ARANESP® (darbepoetin alfa) prescribing information. Disclosure(s): Chanu P is employee and holds stocks in F Hoffmann-La Roche Ltd, was employee of Certara Consulting Services, Certara, Princeton, NJ, USA and contractor to F Hoffmann-La Roche Ltd at the time of this work. Weichert A is employee of F Hoffmann-La Roche Ltd. Schaefer F has received consulting and speaker honoraria from F Hoffmann-La Roche Ltd. Meyer Reigner S is employee of F Hoffmann-La Roche Ltd. Reigner B is employee and holds stocks in F Hoffmann-La Roche Ltd. Frey N is employee of F Hoffmann-La Roche Ltd.